Blockchain and GDPR – A Study on Compatibility Issues of the Distributed Ledger Technology with GDPR Data Processing - Suripeddi, Mani Karthik Suhas; Purandare, Pradnya (Journal of physics. Conference series, 2021)
This research work aims to investigate Blockchain technology and GDPR compliance studies. This will analyze the data privacy perspective with respect to distributed ledger technology. Blockchain has become one of the most frequently discussed technologies for its ability to allow for peer-to-peer transactions without a centralized intermediary. The GDPR was implemented in May 2018 for EU member states to maintain data privacy. DLT, the underlying technology of blockchain as is a decentralized system without any monetary authority. This research conducted a thorough literature review on prior conducted research to investigate the problems and determine the gaps of GDPR compliance with blockchain technologies and discuss the technical, use-case designs or solutions that make blockchain more compliant GDPR in terms of privacy. This systematic literature review addresses the gaps, feasibility, efficiency, and data privacy issues on compatibility problems that are primarily concerned with how a distributed ledger technology system in which recorded data or transaction cannot be changed or erased is challenging the GDPR data subject access rights (DSAR), where every data subject’s personal data which is compliant to GDPR has a right to exercise their Rights to rectify, delete or limit the processing of your personal data at any time if necessary.